2020
DOI: 10.1096/fj.201902103r
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal inflammation downregulates PHD1 expression promoting a barrier‐protective HIF‐1α response in ulcerative colitis patients

Abstract: The HIF hydroxylase enzymes (PHD1‐3 and FIH) are cellular oxygen‐sensors which confer hypoxic‐sensitivity upon the hypoxia‐inducible factors HIF‐1α and HIF‐2α. Microenvironmental hypoxia has a strong influence on the epithelial and immune cell function through HIF‐dependent gene expression and consequently impacts upon the course of disease progression in ulcerative colitis (UC), with HIF‐1α being protective while HIF‐2α promotes disease. However, little is known about how inflammation regulates hypoxia‐respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Relevance to IBD is suggested by studies in experimental colitis models ( Sun et al, 2019 ; Colgan et al, 2020 ; Yin et al, 2020 ), and cell lines ( Muenchau et al, 2019 ; Vissenaekens et al, 2019 ), which indicate a protective stabilization of HIF1α, attenuating mucosal inflammation and promoting barrier formation. Moreover, reagents that activate HIF via inhibition of the prolyl hydroxylase enzymes, are suggested to induce hypoxia-mediated resolution in patients with intestinal mucosal inflammatory disease ( Glover and Colgan, 2011 ; Brown et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevance to IBD is suggested by studies in experimental colitis models ( Sun et al, 2019 ; Colgan et al, 2020 ; Yin et al, 2020 ), and cell lines ( Muenchau et al, 2019 ; Vissenaekens et al, 2019 ), which indicate a protective stabilization of HIF1α, attenuating mucosal inflammation and promoting barrier formation. Moreover, reagents that activate HIF via inhibition of the prolyl hydroxylase enzymes, are suggested to induce hypoxia-mediated resolution in patients with intestinal mucosal inflammatory disease ( Glover and Colgan, 2011 ; Brown et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypoxia restricted to the epithelial surface in animal models of IBD has been observed by using 2-nitroimidazole dyes [ 11 ]. Using endoscopic oximetry, prominent levels of mucosal hypoxia correlated with the degree of inflammation were found in ulcerative colitis (UC) patients [ 12 ]. Contributors to tissue hypoxia in inflamed tissues include increased oxygen consumption by infiltrating immune cells which utilize O 2 to sustain synthesis of inflammatory cytokines and mediators, as well as impaired oxygen supply to these tissues caused by vascular damage, thrombosis, and edema [ 13 ].…”
Section: Hypoxia and Inflammationmentioning
confidence: 99%
“…However, TNF-α treatment reduced HIF-1α protein expression in skeletal muscle myocytes under normoxic conditions [ 63 ]. It was recently shown that under normoxic conditions stimulation of human intestinal epithelial Caco-2 cells with pro-inflammatory cytokines including TNF-α downregulated PHD1 mRNA levels which were correlated with decreased CCAAT-enhancer binding protein (C/EBPα) mRNA and protein expression, suggesting that the effect of TNF-α on the C/EBPα/PHD1 mechanism could lead to increased HIF-1α stabilization in the mucosal tissue of UC patients [ 12 ]. TNF-α treatment also significantly upregulates HIF-1α protein and mRNA levels in human squamous lung A549 and H226 cells, which inhibits A549 cell proliferation and adhesion as well as TNF-α-activated transcriptional activity of HIF-1α, resulting in suppression of vasodilator-stimulated phosphoprotein (VASP) and consequent inhibition of transplanted tumors growth in nude mice [ 64 ].…”
Section: Regulation Of Hif By Cytokinesmentioning
confidence: 99%
“…CCL2 and CXCL8 belong to a family of chemokines, which are mainly involved in immunoregulatory and inflammatory processes [ 43 ]. HIF1A acts as a master regulator of cellular and systemic homeostatic responses to hypoxia and has a regulatory role in intestinal mucosal inflammation in UC patients [ 44 ]. For JUN, it has been confirmed to improve gastrointestinal mucosal conditions in UC patients by modulating JUN-related pathways [ 45 ].…”
Section: Discussionmentioning
confidence: 99%